CLOSEDNESS OF THE OPTIMAL SOLUTION SETS FOR GENERAL VECTOR ALPHA OPTIMIZATION PROBLEMS - Su, T. V.; Hang, D. D. (Journal of Nonlinear Analysis and Optimization: Theory & Applications (JNAO), 2020)
The aim of paper is to study the closedness of the optimal solution sets for general vector alpha optimization problems in Hausdorff locally convex topological vector spaces. Firstly, we present the relationships between the optimal solution sets of primal and dual general vector alpha optimization problems. Secondly, making use of the upper semicontinuity of a set-valued mapping, we discuss the results on closedness of the optimal solution sets for general vector alpha optimization problems in infinite dimensional spaces.